PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN FAST MOVING CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Anggraeni, Putri; Ariyanti, Rizka (Universitas YPPI Rembang, 2023)
Along with the rapid development of the business world, it requires companies to increase their attention to the social environment. Social responsibility is currently getting more and more attention in the business world. This study aims to find out how the effect of Good Corporate Governance, leverage, and profitability on Corporate Social Responsibility (CSR) in Fast Moving Consumer Goods companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Good Corporate Governance is proxied by institutional ownership, independent board of commissioners, audit committee. Leverage is measured by the Debt to Equity Ratio (DER), and profitability is measured by Return on Assets (ROA). The population in this study are Fast Moving Consumer Goods companies in the Food and Beverages sub-sector which are listed on the Indonesia Stock Exchange. Statistical analysis in this study used multiple linear regression analysis and used the IBM SPSS 23 analysis tool. Based on the results of the analysis it can be seen that the audit committee has an effect on Corporate Social Responsibility (CSR), while institutional ownership, independent board of commissioners, Debt to Equity Ratio (DER) and Return on Assets (ROA) have no effect on Corporate Social Responsibility (CSR). While the results of the F test show that all independent variables have an effect on Corporate Social Responsibility (CSR) simultaneously. Keywords : Institutional Ownership, Independent Board of Commissioners, Audit Committee, Leverage, Profitability, and Corporate Social Responsibility (CSR)